21. CHANGES OF SOME BIOLOGICAL INDEX IN THYROID CANCER PATIENTS UNDERGOING SURGICAL TREATMENT AT THAI BINH UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Background: In the world as well as in Vietnam, thyroid cancer accounts for only 1 - 2% of all cancers. Surgery is the method that plays a decisive role, other methods only have an auxiliary role.Periodic follow - up is necessary for patients with thyroid cancer because the disease may recur after treatment.Research objective: To evaluate the change of some biological indicators in thyroid cancer patients undergoing surgical treatment at Thai Binh Medical University Hospital from January 2020 to June 2022.Methods: This is a cross - sectional descriptive study, conducted on 30 thyroid cancer patients treated by surgery at Thai Binh Medical University Hospital. Record the variables: Age, gender, surgical method and some biological indicators before and after surgery.Results: The mean age was 50.4 ± 11.3 years old (29 - 72 years old). Female/male ratio ≈ 6.5/1. 23.3% partial thyroidectomy; 76.7% total thyroidectomy. Before surgery, 100% thyroid hormone was normal. Meanwhile, 100% Thyroglobulin and Anti - Thyroglobulin increased. After 3 months of surgery, 100% had normal blood calcium levels; 100% had a significant decrease in Thyroglobulin and Anti - Thyroglobulin compared to before surgery, only 10.0% had hypothyroidism.Conclusion: Thyroid cancer surgery at Thai Binh Medical University Hospital had good results. After 3 months of surgery, 100% had normal blood calcium levels; 100% had a significant decrease in Thyroglobulin and Anti - Thyroglobulin; only 10.0% had hypothyroidism.
Keywords: Thyroid cancer, thyroid hormone, Thyroglobulin, Anti - Thyroglobulin, Thai Binh Medical University Hospital.